The Effect of Store Atmosphere and Service Quality on Repurchase Intention - Moch Fiqri Alqodri; Santoso Santoso; Keke Shabrina Nurmalitasari (Almana : Jurnal Manajemen dan Bisnis, 2026)
This study is motivated by the rapid growth of the thrifting (used clothing) industry in Indonesia, which has intensified competition among retailers. In such a competitive environment, businesses are required to create a pleasant shopping experience to maintain customer loyalty and encourage repurchase intention. Factors such as store atmosphere and service quality are considered important in influencing consumer behavior, particularly in increasing the likelihood of repeat purchases. This study aims to analyze the effect of store atmosphere and service quality on repurchase intention among consumers of Ob.Second Cirebon Outlet. The research employs a quantitative approach with a causal design. The population consists of consumers who have made purchases at Ob.Second Cirebon Outlet, with a sample of 97 respondents selected using purposive sampling. Data were collected through questionnaires using a 5-point Likert scale and analyzed using multiple linear regression supported by SPSS. The results indicate that both store atmosphere and service quality have a positive and significant effect on repurchase intention, both individually and simultaneously. This implies that creating a comfortable store environment and delivering high-quality service are essential strategies to enhance customer satisfaction and encourage repeat purchases.